ANALYSIS OF THE QUALITY OF VILLAGE-LEVEL CIVIL ADMINISTRATION SERVICES THROUGH THE POPULATION REGISTRATION INFORMATION SYSTEM (SIREP) BY THE TEGAL REGENCY CIVIL REGISTRY SERVICE - Diah Ayu Novitaningrum; Arie Setianging Aji; Fadiya Hayya Salsabila (Program Studi Studi Kependudukan dan Pencatatan Sipil, 2024)
Public services provided by the government to the community must be adjusted to the conditions and needs of the community. The differences in conditions of the community results in diverse services provided by the government. Thus, the Tegal Regency Civil Registry Office made an innovation called the Sistem Informasi Registrasi Penduduk (SIPREP/Population Registration Information System). This research aims to find out about the service quality of civil administration services at the village level through SIREP. The research method used is qualitative descriptive with an inductive approach. The data collection techniques used were observation, interviews, and documentation. To analyze service quality, Sinambela’s theory was used with 6 dimensions of excellent service including transparency, accountability, conditional, participatory, equal rights, and balance of rights and obligations. Based on the analysys results, it was clear that the civil administration services at the village level through SIREP managed by the Tegal Regency Civil Registry Service had been running well. However, there were several inhibiting factors, namely limited human resources, lack of public awareness regarding orderly civil administration, and inadequate facilities and infrastructure in village offices so that services could not be provided in all villages in Tegal Regency. Keywords: Services, Civil Administration, SIREP